Structural performance of cold-formed steel box girders with C-section flanges and sinusoidal corrugated webs. (December 2021) - Wu, Yangwei; Du, Xinxi; Yuan, Huanxin
Abstract: This paper introduces a novel type of cold-formed steel box girder assembled from C-section flanges and sinusoidal corrugated webs, and the structural performance of such box girders was experimentally and numerically investigated. A total of seven cold-formed steel box girder specimens were fabricated by self-drilling screws and were tested subject to three-point bending. Prior to testing, the initial geometric imperfections of the sinusoidal corrugated webs were accurately determined using the 3D optical scanning technique. The structural behaviour of the tested box girder specimens, including load versus displacement curves and corresponding failure modes, was obtained and reported herein. The load-carrying properties of the adopted self-drilling screw connections were examined by separate single lap shear tests. Elaborate finite element (FE) models of the cold-formed steel box girders were developed by ABAQUS and were further validated against the obtained test results. Upon validation of the numerical models, the influences of key parameters including the number of screws, the corrugation ratio a/q, and the initial geometric imperfections were discussed in detail. It has therefore been recommended that the double-screw connections and appropriate corrugation ratios be adopted for design of cold-formed steel box girders with C-section flanges and sinusoidal corrugated webs.